Introduction: Popular Economies and the Remaking of China--Latin America Relations. - Müller, Juliane; Colloredo‐Mansfeld, Rudi (Journal of Latin American & Caribbean Anthropology, 2018)
The article analyzes interdisciplinary field of Latin America-China relations. It is noted that density of trans-Pacific commerce makes a distinctive social and cultural realm of interaction that enablesd new ways for marketplaces to adapt to austere, neoliberal policies. It also discusses growth, rapid adaptability and reversals within street-level commerce in Asian-made goods.